Economic Policy Uncertainty and Stock Market Volatility: A Causality Check - Burkhard Raunig (Oesterreichische Nationalbank (OeNB), 2021)
Using causal graphs, this paper develops a simple check to uncover the direction of the causal link between economic policy uncertainty and stock market volatility. The check is applied to monthly data for 22 countries. The results imply that uncertainty is an instantaneous cause of stock market volatility. Estimates suggest that stock market volatility increases by 0.15% to 0.85% after a 1% increase in economic policy uncertainty.
Keywords: C12; D80; E66; G10; 330; Causal inference; Causal graph; Economic policy uncertainty; Stock market volatility